Lifestyle Behaviors and Suicide-Related Behaviors in Adolescents: Cross-Sectional Study Using the 2019 YRBS Data - Xiaozhi Li (Frontiers Media S.A., 2021)
Objective: The purpose of this research was to investigate the prevalence of lifestyle behaviors and suicide-related behaviors and the association between them using a nationally representative sample of adolescents from the USA.Methods: 13,677 high school students aged 14-18 years were included in this cross-sectional study. The research data were retrieved from the Youth Risk Behavior Surveillance System Survey in 2019. All data on age, sex, grade, race, physical activity, television time, fruit intake, and suicide-related behavior were self-reported by students. Logistic regression models were adopted to examine the association between lifestyle behaviors and the suicide-related behaviors.Results: Students who played video/computer games for ≥2 h had higher risk of suicide attempt (OR = 1.55, 95%CI: 1.30-1.85). Daily sleep duration of ≤8 h was positively associated with considering a suicide attempt (OR = 1.99, 95%CI: 1.62-2.43). In addition, participants who did not engage in any sport team were more likely to report considering a suicide attempt (OR = 1.50, 95%CI: 1.24-1.81).Conclusion: This research suggests that some lifestyle behaviors (e.g., time for video or computer use, sleep duration, sports team participation, regular breakfast intake, and substance use) are associated with increased risk of suicidal behavior and ideation in high school students. To identify the specific effect of multiple lifestyle factors in influencing the risk of suicide-related behaviors in high school students, longitudinal studies are warranted in future.